Suicide and altitude: A systematic review of global literature. Issue 5 (10th May 2022) - Brown, Anne; Hellem, Tracy; Schreiber, James; Buerhaus, Peter; Colbert, Alison
Abstract: Objective: The purpose of this systematic review was to synthesize the existing global literature examining the relationship between altitude and suicide. Method: Using the electronic databases PubMed, CINAHL, EMBASE, and PsychInfo published articles in English that addressed the relationship between altitude and suicide as a primary or secondary aim, and included human subjects, where identified. Studies were assessed for quality based on methodological approach and data relevance on a three‐point scale (strong, moderate, or weak). Results: Of the 19 studies related to the purpose and aims, 17 reported evidence of a positive correlation between altitude and increased suicide. Vast design differences were employed within the literature, individual‐level suicide data was identified as the preferred level of analysis. Discussion: The relationship between altitude and suicide is an evolving science with a small but growing body of literature suggesting altitude is associated with an increased risk of suicide. This review identifies the need for additional studies examining both individual‐level suicide data and improving geographic precision. Public health nurses have a responsibility to carefully examine the quality of studies and the strength of the evidence when addressing variables associated with suicide.